The Sole Mycobacterium smegmatis MazF Toxin Targets tRNALys to Impart Highly Selective, Codon-Dependent Proteome Reprogramming - Barth, Valdir Cristovao; Woychik, Nancy A. (Frontiers in Genetics, 2020)
Survival of mycobacteria, both free-living and host-dependent pathogenic species, is dependent on their ability to evade being killed by the stresses they routinely encounter. Toxin-antitoxin (TA) systems are unique to bacteria and archaea are thought to function as stress survival proteins. Here we study the activity of the endoribonuclease toxin derived from the MazEF TA system in Mycobacterium smegmatis, designated MazEF-ms. We first enlisted a specialized RNA-seq method, 5’ RNA-seq, to identify the primary RNA target(s) of the MazF-ms toxin. Just two tRNA species, tRNALys-UUU and tRNALys-CUU, were targeted for cleavage by MazF-ms at a single site within their anticodon sequence (UUU and CUU) to render these tRNAs nonfunctional. The 5’ RNA-seq dataset also revealed hallmarks of ribosome stalling at Lys AAA codons because both Lys tRNAs were depleted by MazF-ms. Stalled ribosomes were then cleaved on their 5’ side by another unknown RNase, resulting in very selective degradation of only those mRNAs harboring ribosomes stalled at Lys codons. This highly surgical, codon-dependent degradation of mRNA transcripts was validated using quantitative mass spectrometry of proteins that were newly synthesized during MazF-ms expression. The M. smegmatis proteome was altered as predicted, Lys AAA codon-rich proteins were downregulated while Lys AAA codon deficient proteins were upregulated. Analysis of specific subsets of proteins that were up- or down-regulated were consistent with the growth-arrested phenotype of MazF-ms expressing cells. Curiously, the tRNA target and mechanism of action of MazF-ms paralleled that of one atypical MazF toxin in M. tuberculosis, suggesting manipulation of the levels of lysine tRNAs as the preferred conduit for reprogramming the proteomes via ribosome stalling at rare AAA codons in these GC-rich mycobacteria.